Biomass of the forage in Brachiaria decumbens pastures fertilized with nitrogen - Fagundes, Jailson Lara; Fonseca, Dilermando Miranda da; Gomide, José Alberto; Junior, Domicio do Nascimento; Vitor, Claudio Manoel Teixeira; Morais, Rodrigo Vieira de; Mistura, Claudio; Reis, Gilberto da Cunha; Martuscello, Janaina Azevedo (Pesquisa Agropecuaria Brasileira, 2005)
In the last years, the growth dynamics of forage plants has been focused, in order to improve the knowledge of forage yield and distribution process in pasture. The objective of this work was to evaluate the effect of nitrogen fertilization on accumulation of the forage in Brachiaria decumbens Stapf. pastures submitted to the same stocking rate. Treatments consisted of 75, 150, 225 and 300 kg ha-1 yr-1 N applied before the beginning of experimental evaluations, which were performed during summer, autumn, winter and spring of 2002. A randomized block experimental design was used with two replicates. Brachiaria grass showed an increase in the dry matter yield proportionally to nitrogen doses, with higher rates for daily accumulation of leaves, stems and forage yield in summer-spring seasons, while lower rates were shown in the winter. The variation of climatic conditions within yearly seasons changed the rates of leaf accumulation, senescence, and forage yield in the Brachiaria decumbens pasture.